(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Un simbolo religioso - 2. Una laicità pluralista - 3. Modelli di laicità e simboli religiosi - 4. Il crocifisso - 5. …e la sua “democratizzazione” - 6. Bilanciamento e non discriminazione - 7. Tutela e autotutela. The Crucifix back to Supreme Court of Cassation. Notes by amicus curiae. ABSTRACT: The display of a crucifix in the classrooms breaks the separatism principle and, although voted by the majority of the class, is discriminatory versus the unfavorable pupils and teacher. The protection of the freedom of consciency permits the teacher himself in case to displace the icon throughout his lesson.